A Survey of the Relationship Between Serum Cholesterol and Triglyceride to Glaucoma: A Case Control Study - Mohammad Hossien Davari,; Toba Kazemi,; Azame Rezai, (Journal of Basic & Applied Sciences, 2021)
Purpose/Aim: primary Open-angle glaucoma (POAG) is an asymptomatic, progressive optic neuropathy characterized by enlarging optic disc cupping and visual field loss. POAG is a major cause of blindness and is characterized by progressive degeneration of the optic nerve and is usually associated with elevated intraocular pressure. Regarding the fact that dyslipidemia has a relationship with some ophthalmic diseases such as cataract,it sounds that the same relationship also exists with POAG. Therefore, it was decided to study the relationship between serum cholesterol and triglyceride to POAG. Methods: The present study was done on 40 primary Open-angle glaucoma (POAG) patients (cases) and 40 healthy individuals (controls). In order to diagnose POAG, Intra ocular pressure (IOP) was measured by means of Applanation tonometry, and then was confirmed through perimetry and ophthalmoscopes. The controls were patients’ attendants who had referred to Birjand Valli-e-asr clinics but did not have POAG. After a fasting of 12 hours, blood samples were derived to determine serum level of triglyceride and cholesterol levels. Then, the results of the tests together with the participants’ demographic information were individually registered in a questionnaire. The obtained data was analyzed by means of SPSS software (version 15) and statistical tests including T-test and Chi- square. Results: Mean levels of cholesterol (211.18± 51.91mg/dl in cases, 162.38±39.56 mg/dl in controls) and triglyceride (165.92±88.58 mg/dl in cases, 99.46± 43.08 mg/dl in control) were significantly higher in cases than in controls. Hypercholesterolemia and hypertriglyceridemia were significantly higher in the cases compared with the controls. There was a positive association between POAG and dyslipidemia (OR=7.14 [95% CI: 2.3-22.2] for Hypercholesterolemia and OR=16.9 [95% CI: 2.1-14.8] for hypertriglyceridemia. Conclusion: Hyperlipidemia can be a risk factor of getting POAG.